Targeting C–C Chemokine Receptor 5: Key to Opening the Neurorehabilitation Window After Ischemic Stroke - Feng, Yi-Qi; Xu, Zhen-Zhen; Wang, Yan-Ting; Xiong, Yue; Xie, Wanli; He, Yu-Yao; Chen, Lu; Liu, Guo-Yang; Li, Xia; Liu, Jie; Wu, Qingping (Frontiers in Cellular Neuroscience, 2022)
Stroke is the world’s second major cause of adult death and disability, resulting in the destruction of brain tissue and long-term neurological impairment; induction of neuronal plasticity can promote recovery after stroke. C–C chemokine receptor 5 (CCR5) can direct leukocyte migration and localization and is a co-receptor that can mediate human immunodeficiency virus (HIV) entry into cells. Its role in HIV infection and immune response has been extensively studied. Furthermore, CCR5 is widely expressed in the central nervous system (CNS), is engaged in various physiological activities such as brain development, neuronal differentiation, communication, survival, and learning and memory capabilities, and is also involved in the development of numerous neurological diseases. CCR5 is differentially upregulated in neurons after stroke, and the inhibition of CCR5 in specific regions of the brain promotes motor and cognitive recovery. The mechanism by which CCR5 acts as a therapeutic target to promote neurorehabilitation after stroke has rarely been systematically reported yet. Thus, this review aims to discuss the function of CCR5 in the CNS and the mechanism of its effect on post-stroke recovery by regulating neuroplasticity and the inflammatory response to provide an effective basis for clinical rehabilitation after stroke.